Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

The work of SCAR for the conservation of nature in the Antarctic - Gjelsvik, Tore (University of Chile, 1977)
Keywords: Antarktis; fauna; flora; forurensning; kongress; miljø; politikk; symposium; økologi